2011
DOI: 10.1103/physrevb.83.165440
|View full text |Cite
|
Sign up to set email alerts
|

Electron interaction-driven insulating ground state in Bi2Se3topological insulators in the two-dimensional limit

Abstract: We report a transport study of ultrathin Bi 2 Se 3 topological insulators with thickness from one quintuple layer to six quintuple layers grown by molecular beam epitaxy. At low temperatures, the film resistance increases logarithmically with decreasing temperature, revealing an insulating ground state. The sharp increase of resistance with magnetic field, however, indicates the existence of weak antilocalization, which should reduce the resistance as temperature decreases. We show that these apparently contra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
167
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(185 citation statements)
references
References 53 publications
16
167
1
1
Order By: Relevance
“…However, similar transitions were observed even in films with their Fermi levels far above the Dirac point: first by us in Y. Kim et al [45] and later by Taskin et al [47]. Although these studies report that the transition occurs at just below 5 QL, which happens to be close to the gap opening thickness as observed by the ARPES study, whether this is related to the gap opening at the Dirac point is questionable considering that their Fermi levels are far (~300-500 meV) from the Dirac point; disorder and surface scattering in the ultrathin regime can However, Bansal et al [27], Liu et al [52], and Brahlek et al [30] showed that Bi 2 Se 3 films with much higher mobilities did not exhibit such a 1-to-0 transition in Ã, which remained close to 1 all the way down to 2 QL. In Fig.…”
Section: Weak Anti-localizationmentioning
confidence: 86%
See 1 more Smart Citation
“…However, similar transitions were observed even in films with their Fermi levels far above the Dirac point: first by us in Y. Kim et al [45] and later by Taskin et al [47]. Although these studies report that the transition occurs at just below 5 QL, which happens to be close to the gap opening thickness as observed by the ARPES study, whether this is related to the gap opening at the Dirac point is questionable considering that their Fermi levels are far (~300-500 meV) from the Dirac point; disorder and surface scattering in the ultrathin regime can However, Bansal et al [27], Liu et al [52], and Brahlek et al [30] showed that Bi 2 Se 3 films with much higher mobilities did not exhibit such a 1-to-0 transition in Ã, which remained close to 1 all the way down to 2 QL. In Fig.…”
Section: Weak Anti-localizationmentioning
confidence: 86%
“…On the other hand, in the bulk limit shown in (g) at t = 1000 nm, Δ(t) is zero over most of the range of N BD and n SD . [27] and [52] showing that à is ~1 over the entire thickness range without any 1-to-0 transition down to thickness of 2 QL. (b) High mobility, bulk insulating Cu-doped Bi 2 Se 3 films from Ref.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2(d) shows the STM topography of a nominal 3QL thick film with flat terraces and 1 nm step heights, corresponding to one QL. Figure 3(a) shows the two-terminal resistance measured during sample cool-down, which displays an insulating behavior with resistance increasing about two orders of magnitude between room temperature and 5 K. Similar insulating behavior has always been seen in ultrathin Bi 2 Se 3 films, which could be due to strong interactions [25], or Anderson localization [26,27]. To test the gating ability of the TI/STO device, we measured the 2-terminal resistance through the 3QL film vs. gate voltage (Fig.…”
mentioning
confidence: 84%
“…Below E F , the electron-plasmon interaction can lead to reconstruction of the Dirac cone by forming a plasmaron band, which gives a sudden DOS change at Fermi level [33]. This mechanism which depends on interactions far from the Dirac point may remain intact despite the opening of a gap around it [19], and may even be enhanced in ultrathin film geometries [25].…”
Section: (B))mentioning
confidence: 99%
“…Realizing surface dominated transport in current topological insulator systems is still a challenge despite extensive efforts involving chemical doping 22,[33][34][35][36][37][38][39] , thin film or nanostructure fabricating [25][26][27][28][29][30][31][32] and electrical gating 21,26,32 .…”
mentioning
confidence: 99%